Public Input on the Hixon Forest Comprehensive Plan: A Case Study - Harrison, Peter J. (My University, 2004)
Hixon Forest is an 800 acre nature-based park located on the east side of La Crosse, Wisconsin. In 2003, the City of La Crosse Planning Department initiated a project to develop a Comprehensive Plan for Hixon Forest. Because of the large number and wide array of current users of Hixon Forest, public input is desired so that the opinions and concerns of those users can be incorporated into the Comprehensive Plan. An extensive literary search was performed to examine the different methods of public input. Along with this, interviews were conducted with public agency personnel who were experienced in developing and implementing public input strategies. From this information a Public Input Plan is designed for the Hixon Forest Comprehensive Plan that will gather verbal and written input from the stakeholders and users of Hixon Forest and educate those users on the opportunities available in the forest. In the beginning the Public Input Plan states the goals and objectives of the process. Along with this a detailed mission statement establishes the purpose for public input. The roles of the many entities involved are described in this plan as well as their relationship to one another. An overall timeline of events in the process is given so that everyone is able to visualize the public input process in its entirety. Each method of public input is then broken down into its own timeline and bulleted lists are given to describe in greater detail what each method will be used for and what type of information each method will provide. The end of the Public Input Plan offers reminders for different steps in the process and tips for constructing survey questions, which will be used to gather information from participants.
Keywords: Hixon Forest (La Crosse, Wis.) -- Management; Hixon Forest (La Crosse, Wis.) -- Public opinion; Natural areas -- Management